Application of China's CCUS Environmental Risk Assessment Technical Guidelines (Exposure Draft) to the Shenhua CCS Project. (July 2017) - Li, Qi; Li, Xiaying; Liu, Guizhen; Li, Xiaochun; Cai, Bofeng; Liu, Lan-Cui; Zhang, Zhansheng; Cao, Dong; Shi, Hui
Abstract: The environmental risk assessment is an important research content of carbon dioxide (CO2 ) capture, utilization and geological storage (CCUS). In this paper, we firstly addressed the exposure draft of China's Technical Guideline on Environmental Risk Assessment for Carbon Dioxide Capture, Utilization and Storage. Then, we applied this technical guideline to the Shenhua Group's CCS demonstration project located in the Ordos Basin, China. The feature-event-process analysis and risk matrix method were used to evaluate the consequences and the possibility of environmental risks of the project. Finally, through the example of verification, we investigated the applicability and potential problems of this technical guideline. Though the final release of this technical guideline on June 20, 2016 has some notable changes, the whole assessment method and operational procedures of this paper can be used all the time without changes.